Climate and soil nutrients differentially drive multidimensional fine root traits in ectomycorrhizal‐dominated alpine coniferous forests. (11th May 2020) - Ding, JunXiang; Kong, Deliang; Zhang, Ziliang; Cai, Qin; Xiao, Juan; Liu, Qing; Yin, Huajun
Abstract: Fine root traits vary greatly with environmental changes, but the understanding of root trait variation and its drivers is limited over broad geographical scales, especially for ectomycorrhizal (ECM)‐dominated conifers in alpine forests. Herein, the covariation patterns of and environmental controls for fine root traits among ECM‐dominated conifers were examined to test whether and how climate and soil nutrients differentially affect fine root trait variations. Eight traits of first‐ and second‐order roots were measured, that is, root diameter (RD), specific root length (SRL), branching intensity (BRI), root tissue density (RTD), mycorrhizal colonization rate (MCR) and concentrations of carbon (C), nitrogen (N) and phosphorus (P), across 76 alpine coniferous populations on the eastern Tibetan Plateau, China. Our results showed that variations of the fine root traits fell into two major dimensions: the first dimension (32.39% of the total variance) was mainly represented by RD and SRL, potentially conveying a trade‐off between root life span and efficiency of resource foraging; the second dimension (23.70% of the variance) represented coordinated variation for root nutrients (i.e. N and P) and RTD, which depicts the conservation‐acquisition trade‐off in resource uptake, that is, root economic spectrum. Variations in RD and SRL were mainly driven by climatic variables, characterized by a significant increase in RD and a decrease in SRL with increasing mean annual precipitation. In contrast, variations in fine root nutrients (i.e. N and P) and RTD were primarily driven by soil fertility, showing a significant increase in root N and P concentrations but a decrease in RTD with increasing soil resource levels. Synthesis . Our study clearly shows two distinct dimensions of the variation of fine root traits in ECM‐dominated alpine coniferous forests, providing further evidence of the inherent multidimensionality of root traits. Moreover, our findings highlight different roles of climatic and soil variables in driving the variation of fine root traits, potentially leading to the multidimensionality of root traits. This study provides new insights for understanding and predicting shifts in plant belowground strategies in climate‐sensitive alpine forests world‐wide. Abstract : Our study shows two distinct dimensions of the variation of fine root traits in ECM‐dominated alpine coniferous forests on the eastern Tibetan Plateau. The climatic and soil variables drive differently the variation of fine root traits, potentially leading to the multidimensionality of root traits.